ANALISA KINERJA KEUANGAN BUMN SEBELUM DAN SESUDAH PRIVATISASI DI INDONESIA PERIODE 2004-2009 - Sparsa, I Gusti Agung Adi; Widanaputra, Anak Agung G P (E-Jurnal Akuntansi, 2015)
BUMN (Indonesian State-Owned Enterprises) are known to be inefficient and highly dependent on the government bureaucracy; therefore, the government adopted privatization policy. This study was conducted to determine the financial performance of BUMN before and after privatization using BUMN privatized in 2004-2009. The data were analyzed by paired T-test. The liquidity through the current ratio and cash ratio increased insignificantly after privatization. Based on return on investment, the profitability increased while based on return on equity, it decreased insignificantly. In terms of the activity ratio, collection periods decreased significantly while total asset turnover increased insignificantly and the leverage decreased insignificantly.
Keywords: BUMN, Privatisasi, Kinerja Keuangan